Çevreye Minberden Bakmak: Cuma Hutbelerinde Çevre Sorununun Sunumu (Looking to Environment from the Perspective of Pulpit: Presentation of the Issue of Environment in Friday Sermons) - Metin Demir (İnsan & Toplum)
Friday sermons (khutbah)are generally deprived of academic concerns and this situation deserves due investigation since, as a mass medium, they have a sociological and political importance. In this article, sermons are handled through Althusser’s notion of “ideology.” It is asserted that Friday sermons may be considered as one of the state’s ideological apparatuses. The subject of research is an issue of the presentation and use of environment in sermons. The aim for chosing this subject, rather than other major topics such as nationalism, Kemalism et cetera, is to look at a secondary area because ideology displays itself in such kinds of hidden domains. If the sermons published by the Istanbul Müftülüğü in between 2001 and 2011 are analyzed, it will be seen that the discourse used in sermons dramatically changed after a certain date. Whereas earlier sermons represented a swallow, anthropocentric view, later a gradual evolution toward a more eco-centric view is observed. There is a visible tension between religion, the state and ecology which is observed through this process of change. It can be seen that Diyanet (The Presidency of Religious Affairs) seeks to maintain its existence in an uncanny situation between radical Islam, the Turkish Republic’s ideals and traditional Islamic understandings; all while at the same time opening and securing itself a living space through the discussion of ecological issues.